Relationship Between Employee Relations and Performance in Technical Training Institutes in Kenya - Matolo, Rose Syombua; Iravo, Mike; Waititu, Gichuhi A. (Advances in Social Sciences Research Journal, 2019)
The aim of the research was to find out the relationship between employee relations and the employee performance in technical training institutes in Kenya. One of the HRM practice that is key to overall performance of an employee and at large the employer is employee relations. This consists of all those areas of human resource that involve relationships with employees directly or through collective agreements where trade unions are recognized. It embraces interrelationships, both formal and informal between managers and those they manage (Armstrong, 2009). Technical Institutes contribute to the development of any given country. The technical training institutes have in the recent past, faced transformation, expansion, conversions/upgrading and competition from other service delivery organizations. This means that the performance of the employees therein will also be affected in one way or the other. The research adopted both descriptive and correlational research designs. It also used a mixture of methods approach consisting of both qualitative and quantitative research methods, applied to a sample of the technical training institutes in Kenya. A sample size of 3 Technical Institutes in Kenya and 137 respondents was used. A linear regression analysis was used to explain the relationship between independent and dependent variable. The data was analyzed through Statistical package for social sciences and presented using the statistical methods. The results were used test and determine the relationship of the variables. The findings revealed that employee relations respectively had a positive relationship on their performance. Keywords: Human Resource Management, Employee Relations, Performance, Employee Performance, Technical Institutes in Kenya.